2006
DOI: 10.1292/jvms.68.1215
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Prostatic Abscesses by Aspiration of the Purulent Matter and Injection of Tea Tree Oil into the Cavities in Dogs

Abstract: ABSTRACT. Ultrasonography-guided transabdominal needle aspiration was carried out to remove 3 to 14 ml of purulent matter from the cavities of prostatic abscesses in 6 dogs, and the same volume of tea tree oil was injected into the cavities to treat the abscesses. The same treatment was repeated 3 weeks later in 4 dogs, and subsequent disappearance of the purulent matter in the cavities and a marked reduction in the volume of the cavities were observed. These findings indicate that the treatment of prostatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…In addition, supplements containing EOs were shown to have a positive effect on atopic dermatitis [21,22], chronic dermatitis [23], pyoderma [24], nasal hyperkeratosis [25], and malodour in dogs [26]. EOs can also be used as ingredients in mouth rinses for their antimicrobial properties [27,28] or in the treatment of abscesses [29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, supplements containing EOs were shown to have a positive effect on atopic dermatitis [21,22], chronic dermatitis [23], pyoderma [24], nasal hyperkeratosis [25], and malodour in dogs [26]. EOs can also be used as ingredients in mouth rinses for their antimicrobial properties [27,28] or in the treatment of abscesses [29].…”
Section: Introductionmentioning
confidence: 99%
“…Tea tree oil delivered into the cavities of prostatic abscesses in dogs in place of aspirated purulent matter resulted in the disappearance of the purulent matter in the cavities and a marked reduction in the volume of the cavities. 178 The ability of using these antimicrobials for site-specific applications, such as in release-based or non-leaching surfaces remains largely undiscovered. A range of polymer coatings based on ultra-high molecular weight polyethylene, very high molecular weight polyethylene and latex compounds and incorporating a wide range of biocidal phytochemical agents, alone and in combinations, have been proposed, with primary area of application being marine paints and coatings.…”
Section: Plasma-assisted Processing Of Essential Oilsmentioning
confidence: 99%
“…Kawakami 19 reported that progestogens can lead to oligospermia resulting in the production of abnormal spermatozoa and consequently leading to hypofertility in dogs.…”
Section: Treatment Strategiesmentioning
confidence: 99%